The Inheritance Grants without Approval of Any Heirs - Takib Wilman Hakim; Akhmad Khisni; Amin Purnawan (Sultan Agung Notary Law Review, 2021)
The purpose of this study was to find out and analyze the legal considerations of the panel of judges to adjudicate a dispute over the Deed of Grant of Land Rights to one of the prospective heirs without the consent of the other prospective heirs in the Cirebon District Court Decision Number. 18/Pdt.G/2017/PN.Cbn. To find out and analyze the Certainty of the Deed of Grant of Land Rights without the Approval of Prospective Heirs Based on the Compiled of Islamic Law. The method used by the researcher is Empirical Jurisdiction and The specifications in this study are descriptive-analytical. Based on the results of the study that Legal Considerations of the Panel of Judges to adjudicate the Dispute on the Deed of Grant of Land Rights to One of the Prospective Heirs without the Approval of the Other Prospective Heirs it is appropriate to cancel the grant because if it is related to the legislation on grants, it has violated Article 211 KHI which is supported by considering evidence in the form of a certificate of distribution of land/agricultural/housing assets, the statement of the grant cannot be adjusted to the original and the object of the case determined as inheritance cannot be accepted because the inheritance has never been divided with other heirs. Certainty of the Deed of Grant of Land Rights without the Approval of Prospective Heirs Based on the Compiled of Islamic Law on grant in Article 200 of the Compilation of Islamic Law is an act carried out in the context of delivering an item/object from the grantor to the grantee and the goods delivered are his own property.